Inter-individual Variation in Receptor Expression Influences MERS-CoV Infection and Immune Responses in Airway Epithelia - Li, Kun; Wohlford-Lenane, Christine; Bartlett, Jennifer A.; McCray, Paul B. (Frontiers in Public Health, 2022)
Middle East respiratory syndrome coronavirus (MERS-CoV) causes respiratory infection in humans, with symptom severity that ranges from asymptomatic to severe pneumonia. Known risk factors for severe MERS include male sex, older age, and the presence of various comorbidities. MERS-CoV gains entry into cells by binding its receptor, dipeptidyl peptidase 4 (DPP4), on the surface of airway epithelia. We hypothesized that expression of this receptor might be an additional determinant of outcomes in different individuals during MERS-CoV infection. To learn more about the role of DPP4 in facilitating MERS-CoV infection and spread, we used ELISA and immunofluorescent staining to characterize DPP4 expression in well-differentiated primary human airway epithelia (HAE). We noted wide inter-individual variation in DPP4 abundance, varying by as much as 1000-fold between HAE donors. This variability appears to influence multiple aspects of MERS-CoV infection and pathogenesis, with greater DPP4 abundance correlating with early, robust virus replication and increased cell sloughing. We also observed increased induction of interferon and some interferon-stimulated genes in response to MERS-CoV infection in epithelia with the greatest DPP4 abundance. Overall, our results indicate that inter-individual differences in DPP4 abundance are one host factor contributing to MERS-CoV replication and host defense responses, and highlight how HAE may serve as a useful model for identifying risk factors associated with heightened susceptibility to serious respiratory pathogens.